ChemInform Abstract: An Asymmetric Synthesis of trans‐Fused Butyrolactones from Endoperoxides. Issue 33 (25th July 2013) - Priest, Joshua; Longland, Mark R.; Elsegood, Mark R. J.; Kimber, Marc C.
Abstract A convenient and single‐pot method for the synthesis of the title lactones is developed, which also gives access to natural products, e.g. xanthanolide derivative (IX).